Development of damage functions for flood risk assessment in the city of Colombo (Sri Lanka). (2018) - Dias, Priyan; Arambepola, N.M.S.I.; Weerasinghe, Kumari; Weerasinghe, K.D.N.; Wagenaar, Dennis; Bouwer, Laurens M.; Gehrels, Hans
Abstract: Depth vs. damage curves were developed for a flood risk assessment carried out in Colombo, Sri Lanka. The major elements of the damage assessment comprised building fabrics, building contents, distributed infrastructure and vehicles. Current approaches to damage function development were improved on by separating damage to building fabric and contents; using actual building footprints rather than assigning building functions to city zones; assessing infrastructure damage accurately; and incorporating damage to vehicles. Information sources included infrastructure agencies, bills of quantities for buildings, expert consultations, household surveys and insurance agencies. The building fabric was assigned three categories, namely semi-permanent, single storey and two storey. The building contents were classified into 7 types based on function as warehouse/storage, industrial, shops, offices, residential, educational and health. The proportion of contents asset values to that of the fabric ranged from 1.67 for warehouse/storage to 0.20for educational. Both 'what-if' analyses and historic data were used to generate the curves. Data were obtained as losses per unit area or unit length; or as point losses.For the 140 square km urban area, the generated flood damages ranged from USD 37 to 549 million for return periods from 5 to 100 years, with average inundation depths ranging from 0.48 m to 1.28 m (and outliers up to 5.8 m). The total non-residential to residential building damage increased with return period (and together accounted for 75-85% of damage). The residential contents to fabric damage ratio was generally around 1.5. The percentage damage to infrastructure was not very significant, although that to vehicles was, especially at lower return periods.